2020
DOI: 10.1002/ijfe.2373
|View full text |Cite
|
Sign up to set email alerts
|

Independence day: Political risk and cross‐sectional determinants of firm exposure after the Catalan crisis

Abstract: This article covers the relationship of one of the most uncertainty-generating events in the recent history of Spain: the Catalan secessionist crisis, and the equity market. The research analyses the differences between Catalan companies and the rest of the country and it is focused on the determinants of the variability of returns after the illegal independence referendum. Determinants such as firm country risk concentration, measured as the level of internationalization or the growth opportunities, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Explaining the primary "risk factors, causes, levels, and development trends" in a country or region represents the main goal of country risk investigation and assessment [4]. As a multifaceted topic, previous empirical investigations have explored country risk in relation to various contexts, such as environmental issues [5][6][7][8][9], supply chain contexts [10][11][12], and energy [13,14], as well as business contexts related to process effectiveness [15] and firm exposure [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explaining the primary "risk factors, causes, levels, and development trends" in a country or region represents the main goal of country risk investigation and assessment [4]. As a multifaceted topic, previous empirical investigations have explored country risk in relation to various contexts, such as environmental issues [5][6][7][8][9], supply chain contexts [10][11][12], and energy [13,14], as well as business contexts related to process effectiveness [15] and firm exposure [16].…”
Section: Introductionmentioning
confidence: 99%
“…Country risk has also proven to be highly relevant in assessing performance and related activities of banks and financial institutions [1,[17][18][19][20]. To examine country risk and its potential impact on business operations, previous empirical investigations have used a wide range of data analysis techniques, such as Copula [21], regression [6][7][8]10,14,16,17], analytic hierarchy process (AHP) [15], fuzzy sets [8,15,22], Bayesian Belief Network [11], Grey-TOPSIS Model [23], artificial neural networks [24], and principal component analysis [12,25,26]. Nonetheless, no consensus has been reached in proposing a specific methodology and framework.…”
Section: Introductionmentioning
confidence: 99%
“…The first part of this paper looks at the impact of political and economic uncertainty on capital markets. In this regard, many papers have shown that there is a negative relationship between uncertainty and short-term returns (Angosto-Fernández and Ferrández-Serrano, 2020; He et al ., 2017 or Liu et al ., 2017), with similar results after the COVID-19 pandemic (Ashraf, 2020; Fernandez-Perez et al ., 2021 or Liu et al ., 2020), as investors decide to minimise financial exposure until the contingency is resolved (Brown et al ., 1988).…”
Section: Introductionmentioning
confidence: 99%